OP14 Cost Effectiveness Analysis of Salt Reduction Policies to Reduce Coronary Heart Disease in Syria. (10th September 2013) - Wilcox, M; Mason, H; Fouad, F M; Rastam, S; Ali, R Al; Capwell, S; O'Flaherty, M; Page, T F; Maziak, W
Abstract : Background: Coronary heart disease (CHD) and stroke account for approximately half of all-deaths in Syria. The country's CHD mortality rate has escalated by nearly two-thirds between 1996 and 2006, partly reflecting substantial increases in systolic blood pressure (SBP). In high income countries, reduction of dietary salt intake represents a cost effective means of decreasing CHD events via reduced SBP levels. This study aims to assess the potential costs and benefits of implementing contrasting salt reduction policies in Syria, with particular emphasis on the feasibility of policies within the country's socioeconomic and political realities. Methods: A projected 10-year period cost-effectiveness analysis of salt reduction policies was conducted comparing three different approaches: health promotion campaign about salt reduction, labelling of salt content on packaged foods, reformulation of salt content within packaged foods, or a comprehensive strategy involving all three approaches. The incremental cost of a policy was calculated as the sum of CHD-related savings in healthcare costs and the costs of implementing and monitoring the policy, with costs presented in international dollars using 2010 purchasing power parity (PPP) exchange rates. Benefits were defined as life years gained (LYG) due to fewer CHD events. Data sources included existing national resources, international literature, and interviews with local food producers, manufacturers, and government agencies. The effect of salt reduction on SBP was based on review of the literature. Health care costs, LYG and expected CHD events were calculated using the IMPACT CHD model. Sensitivity analyses were conducted to account for the uncertainty in the reduction of salt intake. Results: All policy combinations resulted in LYG when compared to no policy. Health promotion and labelling of salt content were both associated with low private sector costs and large healthcare savings. This resulted in cost savings for both policies alone and the comprehensive approach combining all three policies. Reformulation alone, reformulation plus health promotion, and reformulation plus labelling were not cost saving due to high private sector costs associated with reformulation (+PPP $96, 000, 000). However, the three policy approaches were very cost-effective with incremental costs of $5453 PPP, $2125 PPP, and $2201 PPP per LYG, respectively (well below the region's established cost effectiveness threshold of PPP$12, 250). Conclusion: All salt reduction policies analysed resulted in a reduction of CHD deaths and were either cost-effective or even cost saving. This paper will provide further details concerning the feasibility of such policies in the context of a developing country.